The effect of mucosal-adhesive phytogels “Kvertulin” and “Lekvin” on the state of the oral cavity in patients with helicobacter pylori-associated pathology of gastroduodenal area by the data of dental indices - Bogatu, S. I. (Journal of Education, Health and Sport, 2019)
The article presents information about the state of the oral cavity according to dental indices in patients with chronic gastritis and gastroduodenitis, associated with Helicobacter pylori, before and after eradication therapy. It was shown that dysbiosis and inflammatory changes in periodontal tissues of varying severity develop in patients with chronic gastritis and gastroduodenitis on the background of eradication therapy. The use of antidysbiotic mucous-adhesive phytogels “Kvertulin” and “Lekvin” (which include the prebiotic inulin, the bioflavonoid quercetin, calcium citrate, and the lecithin hepatoprotector as part of “Lekvin”) in the form of applications on the oral mucosa leads to a health condition. PMA index and Mühlemann bleeding index, and “Lekvin” was more effective due to hepatoprotector lecithin introduced in its composition.